1993
DOI: 10.1007/bf01401824
|View full text |Cite
|
Sign up to set email alerts
|

Indications and limitations for CT-guided stereotaxic surgery of hypertensive intracerebral haemorrhage, based on the analysis of postoperative complications and poor ability of daily living in 158 cases

Abstract: The authors have studied the indications and limitations for computerized tomography (CT)-guided stereotaxic surgery (CTGS Surgery) of hypertensive intracerebral haematomas (ICH), based on the analysis of 158 patients in our institutions. Of 158 patients, 120 had putaminal haemorrhage, 21 thalamic, 14 subcortical and 3 in other locations. The patients ranged in age from 37 to 82 years (average 60). Haematoma volume ranged from 8 to 140 ml (average 43). Eleven patients in the series worsened postoperatively bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
1
10
1
1
Order By: Relevance
“…46 Another study reported that 3.8% of the patients, mostly with putaminal or thalamic hemorrhage, had rebleeding after CT-guided stereotactic surgery; 76% had been performed later than 3 days after symptom onset. 47 The rate of rebleeding and the timing of surgery in our cases fell within the ranges of the results of these previous reports, supporting the relative safety of hematoma evacuation surgery in CAA-ICH. Early surgical treatment might have functional and survival advantage for the patients with spontaneous superficial ICH without IVH [48][49][50] ; however, careful consideration of the indication for surgical intervention and perioperative management is still needed, especially for the patients at high risk of surgical intervention.…”
Section: Safety Of Craniotomy and Biopsy In Patients With Caa-ichsupporting
confidence: 88%
“…46 Another study reported that 3.8% of the patients, mostly with putaminal or thalamic hemorrhage, had rebleeding after CT-guided stereotactic surgery; 76% had been performed later than 3 days after symptom onset. 47 The rate of rebleeding and the timing of surgery in our cases fell within the ranges of the results of these previous reports, supporting the relative safety of hematoma evacuation surgery in CAA-ICH. Early surgical treatment might have functional and survival advantage for the patients with spontaneous superficial ICH without IVH [48][49][50] ; however, careful consideration of the indication for surgical intervention and perioperative management is still needed, especially for the patients at high risk of surgical intervention.…”
Section: Safety Of Craniotomy and Biopsy In Patients With Caa-ichsupporting
confidence: 88%
“…The incidence of rebleeding in patients with liver dysfunction is approximately three times greater than that in patients with normal liver function. 2,4,6,15) Fibrinogen is a product of the liver, and liver dysfunction also affects the platelet count and prolonged PT or activated partial thromboplastin time. These factors can be indicators of liver function and hemorrhagic tendency.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical use of stereotactic aspiration for ICH remains controversial. 3,6,12,13) Hematoma evacuation reduces morbidity, shortens hospitalization, promotes the return to activities of daily life, and reduces medical costs. 5) Furthermore, the mortality rate at one month is lower after surgical treatment than after conservative treatment in patients with ICH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principal problem that a strict comparison between surgical and conservative treatment is difficult gave the stratification of severity of the disease [7,16,24,25]. Recently, HPHs are more often operated on by CT-guided stereotaxic surgery instead of conventional open surgery, and many authors stressed the usefulness of this procedure [7,24].…”
Section: Introductionmentioning
confidence: 99%